HUMANISME RELIGIUS DALAM PENDIDIKAN ISLAM - Abdul Rozaq (Universitas Islam Nahdlatul Ulama Jepara, 2015)
Religious humanism is a religious concept that puts human beings as well as the humanization of science with regard to responsibility of hablun minallah and hablum minannas. Implementation This concept is a necessity urgent because of the phenomenon of education that exist as well as the diversity of social hinted religiosity vertical and splendor of the rituals, and social piety is still far from the orientation of our society, and in general the potential of the community has not developed proportionally, independence and responsibility is still a long way in our education. One form of human behavior in educational setting is the birth of social freedom in the child. Social freedom terminology here is that social freedom is essentially limited because humans are social creatures. As social beings, humans have a religious attitude as the basic view of humanity; (1 human tied into an agreement primordial of God, (2 human beings are born in the sanctity of origin, and assumed he would grow in holiness in case no environmental influences, (3 the sanctity of human origin it dwells in the conscience drove him to constantly look for and in favor of the good and true, (4 man is an ethical and moral creature, 5) every human being has a basic right to choose and determine the moral and ethical behavior. Model of atmosphere religious creation is strongly influenced by certain situations and conditions along with the application of the underlying values, namely: a structural model, formal models, models of mechanical and organic models. First, the structural model is the creation of religious fervor inspired by the regulations, the impression development, and policy of an institution or organization and more top-down. Second formal models is namely the creation of a religious atmosphere which builds on the understanding that religious education is a human effort to work on the problems of the afterlife/spiritual course. Third, the mechanical model is the creation of a religious atmosphere that is based on the understanding that education is seen as the establishment and development of a set value of life that runs according to function, which further highlight the moral and spiritual functions or cognitive, affective and psychomotor domains. Fourth, organic models is namely the creation of religious fervor inspired by the view that religious education is the unity that developed a view of religious life and the spirit manifested in the attitudes and skills of religious life.